Triple Bottom Line Model as a Solution for Sustainable Tourism Management in the SAMOTA Area, Sumbawa Regency: Economic, Social, and Environmental Perspectives - Maradita, Fendy; Aprirachman, Rozzy (Universitas Pendidikan Nasional, 2024)
The purpose of this study is (a) To identify and evaluate the internal and external environmental factors of the Samota Tourism Area. (b) To create alternative strategies that can be implemented by the Government and tourism managers to improve tourism competitiveness. (c) Implementation and development of the Triple Bottom Line concept in the Samota Tourism Area. The type of data used in this study is mixed data or mix methods. The combination research method ( mixed methods ) is a research method that combines quantitative and qualitative methods together to obtain more comprehensive, valid, reliable and objective data. The stages of quantitative data analysis were carried out using the Quantitative Strategic Planning Matrix (Qspm) and SWOT analysis with 100 respondents. Qualitative analysis used the Triple Bottom Line (TBL) analysis. The results of the study showed that Internal and External (IE) Matrix is in quadrant IV, indicating that the development of tourism in the Samota area of Sumbawa Regency requires a growth and build strategy . Meanwhile, the SWOT Quadrant Positioning is in quadrant I (positive, positive) indicating that the tourism industry in the Samota area is possible to develop and increase industry growth. Based on the TAS ( Total Attractiveness Score ) Value , the alternative priority strategies that must be implemented are Minimizing environmental damage that has an impact on endemic animals, avoiding activities in protected areas, and the next strategy is to optimize existing tourism potential sustainably and develop supporting infrastructure. The Triple Bottom Line (TBL) analysis shows that tourism development in the SAMOTA area from the Economic dimension shows that increasing economic activity in the tourism sector directly contributes to increasing the income of local people involved in the tourism industry, while from the social dimension it shows that there is a community-based tourism (CBT) approach program to ensure that local people are not only passive beneficiaries, but also become the main actors in tourism development. Meanwhile, from the environmental dimension in the development of the SAMOTA tourism area, it shows that careful planning and implementation of sustainable tourism principles. First, from the perspective of business actors, before the project begins, an Environmental Impact Assessment (EIA) is carried out to identify and mitigate possible environmental impacts.